Data Manipulation and Digital Forensics Analysis on WhatsApp Application - Kucuk, Duzgun; Yakut, Omer Faruk; Ceviz, Baris; Cakar, Emre; Ertam, Fatih (Institute of Electrical and Electronics Engineers Inc., 2022)
WhatsApp is one of the rare applications that has managed to become one of the most popular instant messaging applications all over the world. While inherently designed for simple and fast communication, privacy features such as end-to-end encryption have made confidential communication easy for criminals aiming to commit illegal acts. However, as it meets many daily communication and communication needs, it has a great potential to be digital evidence in interpersonal disputes. In this study, in parallel with the potential of WhatsApp application to contain digital evidence, the abuse of this situation and the manipulation method of multimedia files, which may cause wrong decisions by the judicial authorities, are discussed. The dangerous side of this method, which makes the analysis difficult, is that it can be applied by anyone without the need for high-level root authority or any other application on these devices. In addition, it is difficult to detect as no changes can be made in the database during the analysis phase. In this study, a controlled experimental environment was prepared on the example scenario, the manipulation was carried out and the prepared system analysis was included. The results obtained showed that the evidence at the forensic analysis stage is open to misinterpretation. © 2022 IEEE.
WhatsApp Uygulamasi Üzerinden Gerçekleştirilen Veri Manüpülasyonu ve Adli Bilişim Analizi
15th International Conference on Information Security and Cryptography, ISCTURKEY 2022 -- 19 October 2022 through 20 October 2022 -- Ankara -- 184067
Keywords: Data Manipulation; Digital Forensics; Instant Messaging Applications; Mobile Forensics; Social Media Forensics